Issues and challenges in the development of three-dimensional model for thyroid cancer - Shahbuddin, Munira (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Thyroid is the biggest gland in the body and in case of thyroid cancer, the biological characteristics and prognosis are completely different for different types of thyroid cancer. There are four types of thyroid cancer; papillary, follicular, medullary and anaplastic thyroid cancers. Among these type, anaplastic carcinoma is the rarest and deadliest form of thyroid cancer, often due to poor diagnosis and rapid metastasis. Insignificant differences in preoperative tumor aggressiveness biomarker between each cancer type made slow progress in the development of drug and treatment for thyroid cancer. There have been substantial interest over the past years to develop a 3D human thyroid cancer model for investigation of new therapies. An accurate in vitro model of thyroid cancer with confirmation of the genetic drivers of the cancer will provide an optimal setting for preclinical testing and therapeutics. In this age of personalized medicine, this model can be effective at specializing treatments for the corresponding patients. However, there were reports that mRNA, cytokine and growth factor expression profiles from different type of thyroid cancer cell lines in vitro had shown similarity to the phenotypes of undifferentiated thyroid cancer cells in vivo. The phenotypic similarity of differentiated cell lines in vitro to undifferentiated cells in vivo raised questions on the accuracy and reliability of the spheroid, which is aggregation of cells in spherical form that widely used to mimic tumorigenesis of a cancer model. The use of hydrogel and additional extracellular matrices like fibrinogen and collagen embedded with spheroids and human umbilical vascular endothelial cells (HUVEC) in the 3D model is considered too simple to mimic the physiology and biochemistry of tumorigenesis. The needs for additional growth factors and chemokines in the supplementation affects many aspects of each cell behavior is able to modulate the outcome of the experiment and diagnosis for treatment. Herein, in this review, we would like to discuss in details appropriate in vitro and in vivo conditions of different type of thyroid cancer cells and its relation to physicochemical microenvironment. Despite the paucity of target expression and validation studies on this 3D vascularized model, it is very important that scientists incorporate the basis of cellular biology and materials science in the development of 3D model for therapeutic studies. This should be notable that any slight changes in cellular activities and microenvironment raising the risk of maturation phase in angiogenesis and may influence the outcomes of the treatment.